Tetra-n-propylammonium acetate–boric acid (1/1) - Yang, Yun-Xia (International Union of Crystallography, 2009)
In the crystal structure of the ammonium carboxylate–boric acid cocrystal, (C(3)H(7))(4)N(+)·CH(3)CO(2) (−)·H(3)BO(3), the boric acid forms two O—H⋯O hydrogen bonds to the acetate anion. The acetate–boric acid species is hydrogen bonded to another acetate–boric acid species through the third OH unit of the boric acid about a twofold rotation axis.